2002
DOI: 10.1002/ana.10159
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor‐κB as a molecular target for migraine therapy

Abstract: Nitric oxide (NO) generated from inducible NO synthase (iNOS) participates in immune and inflammatory responses in many tissues. The NO donor glyceryl trinitrate (GTN) provokes delayed migraine attacks when infused into migraineurs and also causes iNOS expression and delayed inflammation within rodent dura mater. Sodium nitroprusside, an NO donor as well, also increases iNOS expression. Because inflammation and iNOS are potential therapeutic targets, we examined transcriptional regulation of iNOS following GTN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(73 citation statements)
references
References 48 publications
2
70
0
1
Order By: Relevance
“…To further corroborate the specific activating effect of TNF-␣ on NF-B, parthenolide (PT), a post-translational inhibitor of NF-B activation (39,40), was used. NF-B binding activity was found to be abolished by PT in a dose-dependent manner in basal or TNF-␣-stimulated conditions (supplemental Fig.…”
Section: Il-1␤ and Tnf-␣ Enhance Nf-b Expression In Fibroblasts-mentioning
confidence: 99%
“…To further corroborate the specific activating effect of TNF-␣ on NF-B, parthenolide (PT), a post-translational inhibitor of NF-B activation (39,40), was used. NF-B binding activity was found to be abolished by PT in a dose-dependent manner in basal or TNF-␣-stimulated conditions (supplemental Fig.…”
Section: Il-1␤ and Tnf-␣ Enhance Nf-b Expression In Fibroblasts-mentioning
confidence: 99%
“…These conditions, including aging [74] , headache [75] , pain [76] , stroke [77] , traumatic brain injury [78] , SCI [79] , Parkinson's disease [80,81] , multiple sclerosis [82] , Alzheimer's disease [83,84] , amyotrophic lateral sclerosis [85] , Huntington's disease [86] , and brain tumors [87][88][89][90][91] , have been associated with the NF-κB pathway. As NF-κB plays important roles in regulating cell survival and death in a broad array of physiological and pathological conditions, it is an attractive proposal to manipulate NF-κB functions to obtain its beneficial effects or abolish its harmful actions when it is required [92] .…”
Section: Nf-κb Inhibitors and Neuroprotective Therapymentioning
confidence: 99%
“…In addition, nitroglycerin induces a decrease of pain threshold at the tail flick and formalin tests in the rat (Tassorelli et al, 2003). Based on the above mentioned as well as other data (Lambert et al, 2000;Reuter et al, 2002;Srikiatkhachorn et al, 2002), the study of the effect of nitroglycerin on the brain and cranial vasculature is now widely accepted as a valid animal model of migraine. Torfgard et al (1989) have demonstrated that subcutaneous nitroglycerin induces the accumulation of NO and cGMP in the rat brain.…”
Section: Introductionmentioning
confidence: 97%